For the given question, let the numbers are = x, y, and z
The sum of three integers is 393 ⇒ x + y + z = 393
The sum of the first and second integers exceeds the third by 39
so, x + y - z = 39
The third integer is 26 less than the first.
So, x - 26 = z
So, we have the following system of equations:
![\begin{cases}{x+y+z=393\rightarrow\left(1\right)} \\ {x+y-z=39\rightarrow\left(2\right)} \\ {x-26=z\rightarrow\left(3\right)}\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/oaxzd5sjzkrnpn47b0m35iolbjx4346nye.png)
Substitute with (z) from equation (3) into equation (2):
![\begin{gathered} x+y-\left(x-26\right)=39 \\ x+y-x+26=39 \\ y=39-26=13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/860wiedr5qajdyqu3ewn8wb2mqmknoavhw.png)
substitute with (y) into the equations (1) and (2)
![\begin{gathered} x+13+z=393 \\ x+13-z=39 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5syh1ihe480j20z6g99hft6uork8tc6s4u.png)
Add the equations to eliminate (z) then solve for (x):
![\begin{gathered} 2x+26=432 \\ 2x=432-26 \\ 2x=406 \\ x=(406)/(2)=203 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ly2bpq192t79gdjqoec8lvmf8uv4bxzh6b.png)
substitute with (x) into equation (3) to find (z)
![z=203-26=177](https://img.qammunity.org/2023/formulas/mathematics/college/7tnyf5mk081qr6l2eq309bp1u8kzonkcxz.png)
so, the answer will be:
![\begin{gathered} x=203 \\ y=13 \\ z=177 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8b3dsdkaqhmud5k8qln7xxcey0up579vb7.png)